WOLFRAM ALPHA AS AN ON-LINE TEACHING TOOL FOR ORDINARY DIFFERENTIAL EQUATIONS SOLVING - CERVENANSKA, Zuzana; KOTIANOVA, Janette (Trends in education, 2012)
Wolfram Alpha is known as a unique web knowledge tool that offers search and visualization of information and it is oriented mainly to science. There are many possibilities how Wolfram Alpha can be used. We have focused on the fact that Wolfram Alpha can be applied also as a tool in math learning process. It is exampled by the theme of differential equations solving. Some ideas for an innovative approach in educational methods supported by Wolfram Alpha are presented in this contribution.
Keywords: Wolfram Alpha; solving of ordinary differential equations; ODE solving; online advanced calculator; answer engin; e-learning; self-instructed study.